Investigation Decision Strategies in JCPOA based on Game Theory Mechanism - Rouhollah Kiani Ghaleh No (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: In this study, the strategies of internal and external decision-makers in Borjam are examined using game theory.Methodology: The decisions made by three related personalities in JCPOA, including the leadership of Iran, the Government of Iran, and the group (1 + 5), were simulated using game theory and analyzed based on the game theory mechanism. In the problem statement section, principles are accepted, and the game is designed based on them. The AHP method was used to evaluate the consequences of the game. The low incompatibility rate calculated for this method describes the evaluation results as acceptable. Entering the negotiations in a static game is expressed with complete information, and the mutual agreement process is shown as a dynamic game.Findings: The game is discussed from two aspects. The pre-game section examines the nature of entering or not entering the negotiations. Examining the game process shows that entering negotiations is strategic for Iran and the group (5 + 1). However, in the main game, strategies for decision-making are examined. Trust without guarantee has been shown to change the game's outcome from win-win to win-lose.Originality/Value: There are various attitudes about JCPOA. In this research, regardless of attitudes and factions, the work process is implemented in a scientific model with a strategic structure.